Image properties for scanning. - Blansit BD (Journal of Electronic Resources in Medical Libraries, 2007)
The modern library is often called on to provide multimedia services such as scanning and transfer of images. To meet this demand, librarians must familiarize themselves with the properties of images and their terminology. This paper briefly presents some of the technical details inherent in scanning images and in choosing image formats. These technical details may also be applied to other imaging technologies. doi:10.1300/J383v04n03_10